Peranan MGMP Sejarah Kebudayaan Islam dalam Meningkatkan Kinerja Guru Tingkat MA di Kota Langsa - M. Zakir (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The Subject Teacher Conference (MGMP) is a forum for meeting subject teachers in schools. The organization was formed as a means of gathering and accommodating various ideas from teachers. This organization is also a means of accommodating various problems faced by teachers in their respective schools. The importance of establishing MGMP in overcoming problems faced by teachers in education units. Through the MGMP, it is expected that teachers can maintain the quality of their performance in carrying out their duties as teachers in accordance with the needs of the community, especially in the world of work. The role of MGMP in the process of improving teacher performance is required to make various breakthroughs that will build quality education. The purpose of this study was to explore several theories about MGMP, and their role in improving the performance of SKI MA teachers in Langsa City, containing the intention of making guidelines in the teaching process so as to be able to produce teachers who have good performance.